Analysis of Rhodamine B on Lip Tint Products Containing Natural Red Color Extracts Using UV-VIS Spectrophotometry - Helmalia, Eulis; Rahmawati, Irma (Pharmaceutical Science and Clinical Pharmacy, 2025)
Rhodamine B is used for textile dyes, paint, paper, or clothing. Rhodamine B is carcinogenic and can trigger the growth of cancer cells if used in the long term, irritating the respiratory tract, eyes, skin, and digestive tract. This study aims to determine the content of Rhodamine B in red natural extract lip tint. Rhodamine B content was determined by thin-layer chromatography and the UV-Vis spectrophotometry method for determining Rhodamine B levels. The identification results showed positive results with Rhodamine B levels in sample B of 8.32 ± 0.18 mg/L, sample C of 17.63 ± 0.35 mg/L, and sample D of 8.99 ± 0.13 mg/L. Based on the results of this study, there is still the use of Rhodamine B as a coloring agent in lip tint that has claims from natural extracts, even though this is prohibited from being used as an additional ingredient in cosmetics by BPOM.